CONSULTA DE ENFERMAGEM AMBULATORIAL EM CARDIOLOGIA:: UMA PESQUISA CONVERGENTE ASSISTENCIAL - dos Santos, Ana Carolina Lobo (2022)
Objective: To build a nursing consultation model for the cardiology outpatient clinic. Method: Qualitative research, which used the methodology of the Convergent Care Survey, with participation of 10 nurses from a cardiology outpatient clinic. Data collection through individual face-to-face interviews and online discussions from the Whatsapp messaging app. The main elements that should be present in the nursing consultation were defined with the outpatient nursing team. Results: As a product of this study, instruments were constructed for outpatient nursing consultations in cardiology. Final considerations: The collective construction of the instruments for the nursing consultation brought reflections on science and care practice, highlighting the existing difficulties and the prospects for improvement.